Do High Schools Choose Financial Education Policies Based on Their Neighbors? - Allison Oldham Luedtke; Carly Urban (Institute of Labor Economics (IZA), 2021)
Financial Education courses required for high school graduation make a difference in students' future financial lives. Given that schools exercise local control, there are a variety of types of courses offered and required by US high schools. It remains unclear why and where this variation exists. Using a novel data set of unique high school personal finance course offerings and requirements paired with distances between high schools in the US, we approximate a network of nearby peer high schools. We use this network of peer schools to measure the potential influence of nearby schools on an individual high school's decision to offer financial education courses. We find that high schools are more likely to require or offer financial education courses similar to those of their peer schools. Having an additional peer that incorporates financial education into their curriculum makes it more likely a high school will change their curriculum to do the same. This is true across types of courses: required standalone courses, required courses that incorporate but do not solely focus on personal finance, and standalone electives. The results indicate that schools' nearby peers are related to what types of services to offer their students, and these networks are more predictive than economic or demographic characteristics of the school in determining personal finance course requirements. Local networks can potentially provide momentum in expanding access to financial education.
Keywords: G53; I20; L14; 330; financial education; financial literacy; networks